2014
DOI: 10.1061/(asce)ae.1943-5568.0000139
|View full text |Cite
|
Sign up to set email alerts
|

State of Integration: Investigation of Integration in the A/E/C Community

Abstract: Integrated buildings are one goal of the architectural/engineering/construction (A/E/C) community. Integration implies quality work and it is perceived to add value to a project; but, how is integration defined and how is it applied? This paper reflects on the current status of integration and assesses where the industry stands. To do this, integration was evaluated through publicly available documents of the major professional organizations that represent the field. The American Institute of Architects; ASCE;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…A recent study, investigating the state of integration in the AEC community concluded that despite the acknowledged importance of integrated practices, integration levels vary among different disciplines (Uihlein, 2013). This study unraveled some of the collaboration issues specific to the building facade sector.…”
Section: Findings and Discussionmentioning
confidence: 76%
“…A recent study, investigating the state of integration in the AEC community concluded that despite the acknowledged importance of integrated practices, integration levels vary among different disciplines (Uihlein, 2013). This study unraveled some of the collaboration issues specific to the building facade sector.…”
Section: Findings and Discussionmentioning
confidence: 76%
“…Delivery of civil infrastructure projects involves collaboration across different kinds of firms including owners, delivery clients, consultants, contractors, and the supply-chain (e.g. Uihlein, 2013). There is a need to synthesize knowledge across their different professional expertise, roles and responsibilities to integrate elements.…”
Section: Introductionmentioning
confidence: 99%